Serious Games for Just Energy Transitions: Theoretical Framework and Application to Enhance Decision-Making for Sustainability - Kioupi,V; Campbell,M; Oluleye,G; Harris,ZM (Sustainability Switzerland, 2026)
Just energy transitions require diverse voices to be considered, but appropriate tools are still lacking. This study aimed to identify a tool by which diverse views could be considered in decision-making for climate change and energy transitions. Specifically, a literature review was conducted to understand the current status and gaps in the use and the application of Serious Games (SGs) in the field of sustainability. This was further used to construct a framework of criteria for selecting SGs that can enable diversity in decision-making. A specific Serious Game was selected using the framework criteria and applied in qualitative analysis that investigated a gameplay and method of data collection and analysis to assess the impact group diversity has on collective decision-making for sustainability and the quality of outcomes produced. The New Shores game was used within the context of sustainability and resilience to climate disasters. A more diverse and a less diverse group (age, ethnicity, gender, and professional role) were recruited in winter 2021, to play the game in online workshops and make decisions to sustainably develop an island while balancing personal and community wellbeing. The way each group engaged with each other and addressed the challenges of the gameplay were qualitatively evaluated to scrutinise levels of collaboration; collective decision-making and the final status of the island was quantitatively analysed to assess quality of outcomes produced by each group. Positive findings indicate that heterogenous groups demonstrated stronger collaboration, prioritised collective goals, and achieved more socially equitable and resilient outcomes compared to homogenous groups. While small scale and exploratory, the positive findings of this study indicate the need for further sustained research into use of Serious Games for sustainability decision-making, to better understand how diverse groups make decisions in game playing contexts and the extent and